2015
DOI: 10.1158/1535-7163.mct-15-0350
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and Acquired Resistance Mechanism of Dovitinib (TKI258) in RET-Rearranged Lung Adenocarcinoma

Abstract: RET rearrangement is a newly identified oncogenic mutation in lung adenocarcinoma (LADC). Activity of dovitinib (TKI258), a potent inhibitor of FGFR, VEGFR, and PDGFR, in RET-rearranged LADC has not been reported. The aims of the study are to explore antitumor effects and mechanisms of acquired resistance of dovitinib in RET-rearranged LADC. Using structural modeling and in vitro analysis, we demonstrated that dovitinib induced cell-cycle arrest at G 0 -G 1 phase and apoptosis by selective inhibition of RET ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…This finding reinforced the lack of requirement for RET signaling and suggested that chronic RET inhibition can suppress phosphorylation independent of ponatinib's ability to bind to the RET kinase domain, perhaps through increased expression of phosphatases or increased turnover of phosphorylated RET. We are not the first to report this phenomenon: dovitinib-resistant LC-2/ad cells with Src activation were also reported to have lost phosphorylation of the RET fusion protein (43). We identified several tyrosine phosphatases that were upregulated in both the PR1 and PR2 cell lines compared to the LC-2/ad control cells: PTPRG, PTPN21, PTPN14, PTPN9, and CDC14A (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…This finding reinforced the lack of requirement for RET signaling and suggested that chronic RET inhibition can suppress phosphorylation independent of ponatinib's ability to bind to the RET kinase domain, perhaps through increased expression of phosphatases or increased turnover of phosphorylated RET. We are not the first to report this phenomenon: dovitinib-resistant LC-2/ad cells with Src activation were also reported to have lost phosphorylation of the RET fusion protein (43). We identified several tyrosine phosphatases that were upregulated in both the PR1 and PR2 cell lines compared to the LC-2/ad control cells: PTPRG, PTPN21, PTPN14, PTPN9, and CDC14A (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, upregulation of 16 coCytokines in lapatinib-treated BT474-J4 vs. DMSO-treated BT474-J4 was also observed, implying a further enrichment of lapatinib-resistant cells or enhanced resistance mechanisms during exposure. We then utilized another dataset (GSE69226) 22 to analyze expression changes of cytokines in LC-2/ad DR (a dovitinib-resistant lung adenocarcinoma cell line) vs. LC-2/ad (a dovitinib-sensitive lung adenocarcinoma cell line). Five of 18 (27.8%) coCytokines showed significant differential expression across these two cell lines ( Figure 6E).…”
Section: Therapeutic Relevance Of Cytokines' Scn Gain and Loss Eventsmentioning
confidence: 99%
“…Dovitinib demonstrated also nanomolar activity againts RET; accordingly, it inhibited proliferation of CCDC6-RET fusion-positive LC-2/ad lung carcinoma cells with an IC 50 of 200 nM (Kang et al 2015). SRC activation was associated to resistance to Dovitinib in these cells (Kang et al 2015). Finally, daily PO dovitinib at 30 mg/kg reduced growth of LC-2/ad xenografts (Kang et al 2015).…”
Section: Novel Investigational Tkis With Activity Against Retmentioning
confidence: 99%
“…SRC activation was associated to resistance to Dovitinib in these cells (Kang et al 2015). Finally, daily PO dovitinib at 30 mg/kg reduced growth of LC-2/ad xenografts (Kang et al 2015). …”
Section: Novel Investigational Tkis With Activity Against Retmentioning
confidence: 99%